Spatiotemporal distribution patterns and exploration implications of multi-type coal-measure gases in the Daniudi gas field, Ordos Basin, China - Zhenrui Bai; Fengcun Xing; Zengqin Liu (Energy Geoscience, 2025)
Coal-measure gas is a primary target with significant potential for the exploration of unconventional hydrocarbon resources. However, the spatiotemporal distribution and combination patterns of multi-type coal-measure gases are yet to be clarified, directly impeding the sweet spot evaluation and exploration deployment of coal-measure gas. This study discussed the characteristics and distribution patterns of coal-measure gases in the Daniudi gas field in northeastern Ordos Basin, China, with abundant drilling data. The results indicate that the coal seams variably thin upward and are mainly seen in the first and second members of the Taiyuan Formation (also referred to as the Tai 1 and Tai 2 members, respectively) and the first member of the Shanxi Formation (Shan 1 Member). Nos. 8, 5 and 3 coal seams are laterally continuous, and significantly thicker in its southern part compared to the northern part. Moreover, carbonaceous mudstones and shales are better developed in the southern part, where limestones are only observed in the Tai 1 Member. Based on the main lithological types, we identified three lithologic roofs of coal seams, that is, limestone, mudstone, and sandstone, which determine the spatiotemporal distribution of coal-measure gases. Besides bauxite gas in the Benxi Formation, the coal-measure gases include tight-sand gas, coalbed methane (CBM), coal-measure shale gas, and tight-limestone gas, with CBM typically associated with coal-measure shale gas. The combinations of different types of coal-measure gas vary across different layers and regions. Tight-sand gas is well-developed in areas where tight sandstones are in contact with coal-measures. From the Taiyuan to the Shanxi formations, CBM gradually transitions into a combination of CBM and coal-measure shale gas, and coal-measure shale gas. Nos.8 and 5 coal seams in low-lying areas exhibit favorable gas-bearing properties due to their large thickness and favorable roof lithologies, serving as prospective play fairways. Mudstone and limestone roofs are more conducive to achieving good gas-bearing properties. The direct contact between sandstones and coal seams tends to result in the formation of tight-sand gas and a reduced gas content of CBM. While focusing on single types of gas reservoirs such as CBM and tight-sand gas, it is essential to consider the concurrent exploration of various coal-measure gas combinations to discover more additional gas resources and guide exploration deployment.